"Suffering in paradise": the difficulties found by mothers in caring for the child with mental distress - Jeferson Barbosa Silva; Camila Carla Dantas Soares; Priscilla Maria de Castro Silva; Elisângela Braga de Azevedo; Alynne Mendonça Saraiva; Maria de Oliveira Ferreira Filha (Universidade Federal de Goias, 2015)
Our objective was to rescue stories of mothers of children with mental distress, to identify what are the difficulties experienced by them, as well as the relationships experienced while caring for their child. This is an exploratory, descriptive and qualitative research, conducted at a CAPSi in the city of Campina Grande/PB/Brazil. The sample was composed by five mothers of children with mental distress. The material was produced by semi-structured interviews and Thematic Oral History. Results were expressed in four thematic axes: 1) Child's limitation and isolation; 2) Nullification of "being" a woman, to the permanent "being" a mother; 3) "A lonely fight": the woman as the main care provider for their children; 4) Difficulties of acceptance by the family and prejudice from society. Difficulties from physiological and social nature were identified. It is necessary to build social support networks, more community care and support to these mothers.